Evaluation of the Online Mode-Based the Candidate of Headmaster Training Program by Using the Kirkpatrick Evaluation Model - Marinu Waruwu (Universitas Pendidikan Ganesha, 2021)
Educational institutions must have creative innovation so that education management continues to run optimally. One of the innovations is the online model-based training of school principal candidates. The objective of this study is to analyze the Effectiveness of the Online Mode-Based Principal Training Program Using the Kirkpatrick Evaluation Model. The training evaluation using the Kirkpatrick model used 4 (four) levels, they were 1) reaction; 2) learning; 3) behavior; 4) results. The research method used was a combination (mixed method). The sample of this research was the training participants of prospective principals, totaling 12 people. Data collection techniques included questionnaires, interviews, observations, and documentation studies. The data analysis technique was carried out by quantitative descriptive and equipped with qualitative analysis based on the results of interviews, observations, and documentation studies. The results show that the success rate of training for prospective principals at all levels is in a good category. The success rate at each level is as follows: 1) evaluation of the participant's reaction level is in the good category level; 2) evaluation of learning level is in good category level; 3) evaluation of behavior level is in good category level; 4) evaluation results are in the good category level, in other words, training has an impact on school development. The results of this study are used as material for evaluating the effectiveness of training for prospective principals and as input for the development of community service programs in the future.